La implementación de un régimen especial de insolvencia para las MYPE - Lizárraga Vera-Portocarrero, Anthony (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
In Peru, small companies have many difficulties to access financial services; therefore, a possible solution is to have a special regime for these companies, which grants a higher expectative of payment to creditors compared with the traditional bankruptcy system, because this access to services provided by financial intermediaries becomes essential for the stability and progress of the sector.

Las micro y pequeñas empresas en el Perú tienen dificultades para acceder a los servicios financieros, en ese sentido, una solución a este problema es que exista un régimen concursal propio para estas empresas que otorgue una mayor expectativa de cobro a sus acreedores a diferencia del sistema concursal tradicional, toda vez que el acceso a los servicios que ofrecen los intermediarios financieros deviene en esencial para la estabilidad y progreso del sector.
Implementation of a special insolvency regime for small companies
Keywords: MYPE; Régimen concursal; Créditos; Deuda; Sistema financiero; https://purl.org/pe-repo/ocde/ford#5.05.00